SPURRING INNOVATIVE WORK BEHAVIOR BY OPTIMIZING PERSON-ENVIRONMENT FIT, PROACTIVE PERSONALITY, AND TRANSFORMATIONAL LEADERSHIP - Maharani, Sagita Dika; Anjaningrum, Widiya Dewi (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
The cafe and restaurant sector has grown quickly in Malang City, thus in order to be competitive, entrepreneurs must have employees who exhibit innovative work behavior. The purpose of this study is to examine the effects of person-environment fit, proactive personality, and transformational leadership on innovative work behavior among Vosco Group workers. Fifty Vosco Group employees were chosen as respondents from the entire population using the saturation sampling technique. The Sem-PLS 4.1.0.8 application was used for data analysis. The results showed that innovative work behavior is significantly impacted by person-environment fit, proactive personality, and transformational leadership. This study recommends more research with a bigger sample size to give organizations more thorough advice on how to use innovation to boost performance and competitiveness.